THE IMPLEMENTATION OF KNOW-WANT-LEARN (K-W-L) STRATEGY IN TEACHING READING AT ELEVENTH GRADE OF SMA NEGERI 3 SINGARAJA - I.P.K.A.P, Putra (International Journal of Language and Literature, 2019)
This study aimed at describing the implementation of Know-Want-Learn (K-W-L) strategy used by one of the English teachers in SMA Negeri 3, Singaraja, Bali. In this study, the subjects of the study were the students of SMA Negeri 3 Singaraja especially the eleventh grade, and, an English teacher. The present study employed qualitative design. The methods of data collection were classroom observation and, questionnaire. The findings showed that there were 3 stages of the implementation of Know-Want-Learn (K-W-L) strategy in SMA Negeri 3 Singaraja namely pre-teaching, whilst-teaching and post-teaching. There were several activities from each stage. In pre-teaching, teachers prepare teaching materials and also media to implement K-W-L strategies. In whilst-teaching, in this stage the teacher implements steps from K-W-L. The result of the questionnaire, showed that Know-Want-Learn (K-W-L) strategy is one of the brilliant alternative strategy that could be used by teacher, because KWL (Know, Want, Learn) developed some ideas about the text before reading the whole text, and focus on finding the important points of the text. It means before the student starts to read the text, they need to use their prior knowledge and continue to set their want or interest of the text.